2020
DOI: 10.1002/chem.201905384
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Structural Changes of Copper Hexacyanoferrate Used as a Cathode in Zn‐Ion Batteries

Abstract: The structural changes of copper hexacyanoferrate (CuHCF), a Prussian blue analogue, which occur when used as a cathode in an aqueous Zn‐ion battery, are investigated using electron microscopy techniques. The evolution of ZnxCu1−xHCF phases possessing wire and cubic morphologies from initial CuHCF nanoparticles are monitored after hundreds of cycles. Irreversible introduction of Zn ions to CuHCF is revealed locally using scanning transmission electron microscopy. A substitution mechanism is proposed to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
(32 reference statements)
4
31
0
Order By: Relevance
“…However, Mantia and co-workers failed to find Cu and Fe elements in the electrolyte through ICP-MS analysis [127]. For this phenomenon, Lim and co-workers claimed that the inserted Zn 2+ not only existed in the interstitial lattice vacancy but also appeared in the pre-occupied lattice site during the cycling process [128]. Zn atoms in the crystal structure will replace Cu atoms, leading to the formation of Cu(CN) 2 and CuZn(CN) 4 .…”
Section: Pbas For Aqueous Zn 2+ Batteriesmentioning
confidence: 99%
“…However, Mantia and co-workers failed to find Cu and Fe elements in the electrolyte through ICP-MS analysis [127]. For this phenomenon, Lim and co-workers claimed that the inserted Zn 2+ not only existed in the interstitial lattice vacancy but also appeared in the pre-occupied lattice site during the cycling process [128]. Zn atoms in the crystal structure will replace Cu atoms, leading to the formation of Cu(CN) 2 and CuZn(CN) 4 .…”
Section: Pbas For Aqueous Zn 2+ Batteriesmentioning
confidence: 99%
“…In previous studies, new diffraction peaks were reported in similar CuHCF cathodes, which are currently thought to be related to these new ZnHCF (or mixed Zn x Cu 1– x HCF) phases caused by the irreversible trapping of Zn 2+ ions inside the framework. 30 , 32 , 34 These peaks usually appear at later stages of cycling (typically after ∼250–500 cycles), along with clear morphological changes, where both wires and cubes have been reported. Here, we do not observe any changes in the morphology, and the new diffraction peaks that appear at relatively early stages of cycling do not match with the proposed Zn x Cu 1– x HCF phases.…”
Section: Resultsmentioning
confidence: 98%
“… 28 , 29 , 32 , 33 These phases are thought to be responsible for new X-ray diffraction (XRD) peaks that appear with cycling, although some of the peaks have not yet been conclusively identified. 28 , 30 , 34 The Zn 2+ trapping and formation of new Zn-rich phases have been proposed to be responsible for shifting the Zn + ion insertion (or the charge/discharge voltage plateaus) to higher potentials. 29 , 32 Nevertheless, uncertainties still remain around both the mechanism of Cu dissolution and the origin of these new diffraction peaks, especially at early stages of cycling.…”
Section: Introductionmentioning
confidence: 99%
“…[ 75 ] Recently, Mantia and Scheu et al demonstrated the emergence of Zn x Cu 1‐ x HCF wire and cubes on the cathode surface upon cycling by scanning electron microscopy (SEM), suggesting morphological conversion of CuHCF during reactions with Zn 2+ ( Figure ). [ 76 ] Scanning transmission electron microscopy–energy dispersive X‐ray spectroscopy (STEM–EDS), and electron energy loss spectra (EELS) of the Zn x Cu 1‐ x HCF further reveal regions with rich Cu, moderate Zn, but almost no Fe adsorption, signaling the formation of Cu(CN 6 ) and ZnCu(CN 6 ). These two products are suspected to be inactive toward Zn 2+ storage and thus the primary reason for the capacity degradation.…”
Section: Prussian Blue Analoguesmentioning
confidence: 99%